Outcome analysis of ventriculoperitoneal shunt procedures in hydrocephalus due to tubercular meningitis and non-infective cases - Tyagi, Devendra K.; Balasubramaniam, Srikant; Jayaswal, Shalika A.; Savant, Hemant V.; Gandhi, Anish S. (International Journal of Contemporary Pediatrics, 2016)
Background:Hydrocephalus is one of the most common clinical conditions affecting the central nervous system. There have been several studies which show that the outcome of VP shunt in tubercular meningitis hydrocephalus is worse. We have conducted the present study to find whether VP shunt procedure complication rates are different in these two sub class patients or if the prognosis in TBM patients is worse due to the primary disease process. Methods: Ours is a retrospective analysis conducted in a tertiary care centre of 50 patients each of hydrocephalus due to tubercular meningitis (TBM) and non-meningitis patients. The data was collected over a period of 3 years. The diagnosis of tubercular meningitis was established by clinical history with examination, cerebrospinal Fluid (CSF) analysis and computed tomography brain (CT - Plain and contrast). All patients underwent Ventriculo Peritoneal shunt (VPS) in a standard protocol. All patients of TBM were put on 4 drugs anti Kochs treatment (AKT) for 3 months and 2 drugs AKT for 1 year. The follow up ranged between 3 years to 6 years. Results:Data in the form of age, sex, clinical signs/symptoms and shunt related complications were noted in a prescribed format. The complications in the two groups were statistically compared for significance using p value. Conclusions:There is no statistically significant increase in complication rate of VP shunt in TBM patients versus non infective cases. The worse prognosis of TBM patients may probably be due to the primary disease process rather than functioning of shunt.